(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2026)
Cyber Secure transmission of sensitive information has become a critical requirement in modern cyber and defense communication systems. Conventional encryption techniques provide strong protection; however, they remain vulnerable when attackers gain access to encryption keys or intercept encrypted files. To address this limitation, this paper proposes a Multi-Security Image Cyber Model designed for highly confidential data transmission environments such as military communication networks.The proposed framework introduces a multi-image based security architecture where a set of five cover images is initially collected and processed. From this set, three images are dynamically selected using a controlled selection mechanism to reduce predictability. Sensitive data is then embedded within the selected images using a matrix-based embedding structure. The system generates a single reconstruction password at a predefined reference point, which acts as the unified key required to combine the three images and recover the hidden information.Unlike conventional methods that rely on a single encrypted carrier, the proposed model distributes security parameters across multiple images and integrates them through a tri-component reconstruction process. Even if an adversary intercepts the transmitted images or partially discovers the authentication key, reconstructing the original confidential data remains extremely difficult because the security structure depends on the correct image combination and reconstruction point. The proposed approach offers enhanced resistance against brute-force attacks, interception threats, and unauthorized decoding, while maintaining efficient transmission performance. The architecture demonstrates a flexible and robust security model suitable for applications requiring high confidentiality, controlled reconstruction, and multi-layer cyber protection